2014
DOI: 10.1175/jcli-d-12-00830.1
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of the Present and Late-Twenty-First-Century Western North Pacific Tropical Cyclone Activity Using a Regional Model

Abstract: A high-resolution regional atmospheric model is used to simulate present-day western North Pacific (WNP) tropical cyclone (TC) activity and to investigate the projected changes for the late twenty-first century. Compared to observations, the model can realistically simulate many basic features of the WNP TC activity climatology, such as the TC genesis location, track, and lifetime. A number of spatial and temporal features of observed TC interannual variability are captured, although observed variations in bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 53 publications
5
59
0
Order By: Relevance
“…A number of previous studies have explored relationships between WNP TC track characteristics and anthropogenic climate change and have identified systematic shifts in TC genesis location and steering flow that combine to cause TC track shifts (Wu and Wang 2004;Li et al 2010;Wang et al 2011;Murakami et al 2011Murakami et al , 2012Yokoi et al 2013;Bell et al 2013;Mori et al 2013;Manganello et al 2014;Wu et al 2014;Colbert et al 2015;Mei et al 2014Mei et al , 2015Roberts et al 2015;Wang and Wu 2015). There is, however, some divergence among the model projections in some of these studies.…”
Section: Projected Changes In Wnp F Lmi and Associated Changes In Tc mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of previous studies have explored relationships between WNP TC track characteristics and anthropogenic climate change and have identified systematic shifts in TC genesis location and steering flow that combine to cause TC track shifts (Wu and Wang 2004;Li et al 2010;Wang et al 2011;Murakami et al 2011Murakami et al , 2012Yokoi et al 2013;Bell et al 2013;Mori et al 2013;Manganello et al 2014;Wu et al 2014;Colbert et al 2015;Mei et al 2014Mei et al , 2015Roberts et al 2015;Wang and Wu 2015). There is, however, some divergence among the model projections in some of these studies.…”
Section: Projected Changes In Wnp F Lmi and Associated Changes In Tc mentioning
confidence: 99%
“…There is, however, some divergence among the model projections in some of these studies. While some high-resolution climate models (usually forced with fixed sea surface temperature) show a poleward shift that is generally attributed to the expansion of the tropics (e.g., Murakami et al 2012;Wu et al 2014), other modeling studies emphasize an eastward shift of the TC tracks toward the central Pacific (Li et al 2010;Murakami et al 2011;Yokoi et al 2013;Mori et al 2013). In some cases, northward and eastward shifts occur FIG.…”
Section: Projected Changes In Wnp F Lmi and Associated Changes In Tc mentioning
confidence: 99%
“…A number of studies demonstrated high skill of atmospheric regional climate models (RCMs) to downscale meso-scale features of TCs (Feser and von Storch 2008a, b;Walsh et al 2004;Knutson et al 2007;Wu et al 2014;AuYeung and Chan 2012;Huang and Chan 2014). Although simulated TC intensities are often too small compared to observed values, they are still more realistic than those in global reanalyses.…”
Section: Introductionmentioning
confidence: 99%
“…Knutson et al (2007) showed that dynamical downscaling of NCEP atmospheric reanalyses with an 18-km grid RCM utilizing spectral nudging, successfully reproduces the observed interannual TC variability over the North Atlantic basin between 1980 and 2006. Wu et al (2014) followed the approach of Knutson 2007 for the western North Pacific. But the authors were not able to reproduce the interannual variability of TC activity, mostly due to a weak/absent relationship with ENSO (Camargo et al 2007;Wang and Chan 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other CMIP5 analyses (Camargo 2013;Tory et al 2013;Murakami et al 2014) project a reduction of global TC frequency by the end of the twentyfirst century for most models. Regional changes in TC frequency are more uncertain (e.g., Knutson et al 2008;Villarini andVecchi 2012, 2013;Knutson et al 2013;Wu et al 2014). …”
Section: Introductionmentioning
confidence: 99%